2018
DOI: 10.1002/htj.21376
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on heat transfer enhancement of nanofluids flow in ribs tube using CFD simulation

Abstract: This study presents, a numerical investigation of two‐dimensional turbulent nanofluids flow in different ribs tube configurations on heat transfer, friction, and thermal performance coefficients using ANSYS‐FLUENT software version‐16. Governing equations of mass, momentum, and energy have been solved by means of a finite volume method (FVM). Four types of nanoparticles namely; Al2O3, CuO, SiO2, and ZnO with volume fraction range (1%‐4%) and different size of nanoparticles (dp = 30 nm, 40 nm, 50 nm, and 60 nm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Metal oxide nanoparticles are used in the present work because they are the most employed in heat transfer applications due to their low cost. They are produced by conventional methods and are more stable than metallic nanoparticles . Three types of oxide metal nanoparticles are studied: Aluminum oxides (Alumina), Al 2 O 3 ; Titanium oxides (Titania), TiO 2 ; and Copper oxides, CuO .…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxide nanoparticles are used in the present work because they are the most employed in heat transfer applications due to their low cost. They are produced by conventional methods and are more stable than metallic nanoparticles . Three types of oxide metal nanoparticles are studied: Aluminum oxides (Alumina), Al 2 O 3 ; Titanium oxides (Titania), TiO 2 ; and Copper oxides, CuO .…”
Section: Experimental Datamentioning
confidence: 99%
“…They are produced by conventional methods and are more stable than metallic nanoparticles. 39 Three types of oxide metal nanoparticles are studied: Aluminum oxides (Alumina), Al 2 O 3 40 ; Titanium oxides (Titania), TiO 2 ; and Copper oxides, CuO. 41,42 The corresponding thermophysical properties of the base fluid (water) 43 and solid phases are given in Table 2.…”
Section: Experimental Datamentioning
confidence: 99%
“…Various researchers have performed the experiments on the thermal performance of various corrugated tubes with pitch ranges from 2 to 64 mm. Studies have also been done for the various diameter ratios range from 0.31 to 0.59.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers [20][21][22][23][24][25][26][27][28][29] have performed the experiments on the thermal performance of various corrugated tubes with pitch ranges from 2 to 64 mm. Studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] have also been done for the various diameter ratios range from 0.31 to 0.59.…”
Section: Introductionmentioning
confidence: 99%
“…Their review showed that the heat transfer enhancement increases due to increase Reynolds number and they also introduced some new configurations of backward and forward facing steps. Salman conducted a comparative study to investigate the heat transfer of nanofluid flow in rib tubes. He used three different types rib, namely, triangular, trapezoidal, and rectangular.…”
Section: Introductionmentioning
confidence: 99%